Barriers to and advantages of e‐health from the perspective of elderly people: A literature review - Arief, Muzawir; Hai, Nguyen Thi Thanh; Saranto, Kaija (Finnish Journal of eHealth and eWelfare, 2013)
e‐Health has created many opportunities to solve the problems of care services and to address the other emerging issues of aging society. This paper aims to understand the advantages of and barriers to e‐Health for elderly people from their perspective. It applies SWOT analysis to categorize the findings in the literature review based on four criteria; Strengths, Weaknesses, Threats and Opportunities. This can be used as a framework for strategy formulation on e‐Health for elderly people in future research. The great strengths of e‐Health in the view of senior citizens lie in improved access to healthcare services and potential cost saving benefits. As a result, a positive attitude is found in most participants surveyed in previous studies. However, its significant weaknesses are the lack of evidence‐ based research to prove its benefits and physical limitations the elderly experience in using high technology. In addition, the quality of e‐Health is still questionable compared to that of traditional services. The study shows that the main threats include data protection, privacy and the digital divide. Finally, the opportunity to implement e‐Health for senior citizens is still promising since better economic growth, education, technological advancement, and improvement in evidence‐based practices in health informatics can prove the effectiveness of e‐Health. This paper emphasizes that the weaknesses and threats can be overcome by utilizing the strengths, and harnessing the potential of e‐Health.